Images of Youth on Screen: Manipulative Translation Strategies in the Dubbing of American Teen Films (Altre Modernità, 2016)
Teen films have often been a locus of censorial intervention due to the sensitive issues that youth-centred stories most typically address, especially when it comes to the representation of family life, juvenile delinquency, violence, youth sexuality and language. This paper offers an analysis of the dubbed versions of three mainstream youth films from the 1950s, 1960s and 1970s, namely Rebel Without a Cause (Nicholas Ray, 1955), Splendor in the Grass (Elia Kazan, 1961) and The Summer of 42 (Robert Mulligan, 1971), with the aim to investigate whether the strategies adopted in their linguistic transfer were shaped by censorial concerns or by differences in the way juvenile cultures were represented locally. The study is based on documentary evidence gleaned from archival research and translator manuscript analysis (Munday 2012, 2013).